A genomic meta-analysis of clinical variables and their association with intrinsic molecular subsets in systemic sclerosis. (25th June 2022) - Franks, Jennifer M; Toledo, Diana M; Martyanov, Viktor; Wang, Yue; Huang, Suiyuan; Wood, Tammara A; Spino, Cathie; Chung, Lorinda; Denton, Christopher P; Derrett-Smith, Emma; Gordon, Jessica K; Spiera, Robert; et al.
Abstract: Objectives: Four intrinsic molecular subsets (inflammatory, fibroproliferative, limited, normal-like) have previously been identified in SSc and are characterized by unique gene expression signatures and pathways. The intrinsic subsets have been linked to improvement with specific therapies. Here, we investigated associations between baseline demographics and intrinsic molecular subsets in a meta-analysis of published datasets. Methods: Publicly available gene expression data from skin biopsies of 311 SSc patients measured by DNA microarray were classified into the intrinsic molecular subsets. RNA-sequencing data from 84 participants from the ASSET trial were used as a validation cohort. Baseline clinical demographics and intrinsic molecular subsets were tested for statistically significant associations. Results: Males were more likely to be classified in the fibroproliferative subset ( P  = 0.0046). SSc patients who identified as African American/Black were 2.5 times more likely to be classified as fibroproliferative compared with White/Caucasian patients ( P  = 0.0378). ASSET participants sera positive for anti-RNA pol I and RNA pol III autoantibodies were enriched in the inflammatory subset ( P  = 5.8 × 10 −5, P  = 9.3 × 10 −5, respectively), while anti-Scl-70 was enriched in the fibroproliferative subset. Mean modified Rodnan Skin Score (mRSS) was statistically higher in the inflammatory and fibroproliferative subsets compared with normal-like ( P  = 0.0027). The average disease duration for inflammatory subset was less than fibroproliferative and normal-like intrinsic subsets ( P  = 8.8 × 10 −4 ). Conclusions: We identified multiple statistically significant differences in baseline demographics between the intrinsic subsets that may represent underlying features of disease pathogenesis (e.g. chronological stages of fibrosis) and have implications for treatments that are more likely to work in certain SSc populations.